1988
DOI: 10.1103/physrevb.38.8562
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-enhanced diffusion in amorphous Pd-Cu-Si

Abstract: Diffusion during He, Ne+, and Xe+ irradiations of trace amounts of Au in melt-spun amorphous Pd78Cu6Si, 6 has been experimentally investigated. Diffusion constants were measured by following the changes in ion-implanted Au profiles with Rutherford-backscattering spectrometry.Heat treatments and simultaneous irradiations were performed as a function of temperature (533-588 K), ion flux, and ion mass. Total integrated fluences being very small, ion-beam-mixing effects are negligible. More than an order of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, there is limited understanding in the possible mechanisms for RED in SiC GBs. For highly disordered GBs, that can be considered approximately amorphous (high-angle GBs), the literature on RED in amorphous materials [71][72][73][74][75] strongly suggests that radiation can change diffusional behaviors. These previously proposed mechanisms includes the collective diffusion via displacement chains [74], enhancement in radiation-induced destabilized regions [71][72][73], and enhancement by increase of free volume from irradiation [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited understanding in the possible mechanisms for RED in SiC GBs. For highly disordered GBs, that can be considered approximately amorphous (high-angle GBs), the literature on RED in amorphous materials [71][72][73][74][75] strongly suggests that radiation can change diffusional behaviors. These previously proposed mechanisms includes the collective diffusion via displacement chains [74], enhancement in radiation-induced destabilized regions [71][72][73], and enhancement by increase of free volume from irradiation [75].…”
Section: Discussionmentioning
confidence: 99%
“…For highly disordered GBs, that can be considered approximately amorphous (high-angle GBs), the literature on RED in amorphous materials [71][72][73][74][75] strongly suggests that radiation can change diffusional behaviors. These previously proposed mechanisms includes the collective diffusion via displacement chains [74], enhancement in radiation-induced destabilized regions [71][72][73], and enhancement by increase of free volume from irradiation [75]. Although there are still many uncertainties about these mechanisms, it is suggested that a RED of Ag through a percolating network of amorphous-like HEGBs may explain the observed radiation effects on Ag diffusion in SiC.…”
Section: Discussionmentioning
confidence: 99%
“…For highly disordered GBs that can be considered approximately amorphous (high-angle GBs), the literature on RED in amorphous materials strongly suggests that RED is likely. Diffusivities of impurities in various disordered (amorphous) materials can be enhanced by orders of magnitude due to irradiation [67][68][69][70][71][72][73]. Specifically, irradiation may increase the pre-factor [67][68][69] or decrease the activation energy [70][71][72][73] of the impurity diffusivity, depending on the diffusion mechanism.…”
Section: Discussion On Mechanisms Of Radiation Enhanced Diffusionmentioning
confidence: 99%
“…Diffusivities of impurities in various disordered (amorphous) materials can be enhanced by orders of magnitude due to irradiation [67][68][69][70][71][72][73]. Specifically, irradiation may increase the pre-factor [67][68][69] or decrease the activation energy [70][71][72][73] of the impurity diffusivity, depending on the diffusion mechanism. Mechanisms proposed for amorphous RED include changes in mediating point defect concentrations [72], irradiation impacting collective diffusion [74], and coupling to free volume [73].…”
Section: Discussion On Mechanisms Of Radiation Enhanced Diffusionmentioning
confidence: 99%
“…Early in 1972 Chen et al 3 found that the addition of Cu can significantly improve the thermal stability of Pd-Si MGs. As a result, the Pd 78 Cu 6 Si 16 MG, which lies close to the eutectic point of the ternary system has attracted interest due to a combination of excellent GFA, outstanding mechanical properties and promising hydrogen sensing ability 4 5 6 7 8 9 .…”
mentioning
confidence: 99%